2014
DOI: 10.1080/14703297.2014.956780
|View full text |Cite
|
Sign up to set email alerts
|

The continuing search to find a more effective and less intimidating way to teach research methods in higher education

Abstract: Existing literature examining the teaching of research methods highlights difficulties students face when developing research competencies. Studies of student-centered teaching approaches have found increased student performance and improved confidence in undertaking research projects. To develop a student-centered approach, it could be beneficial to teach students through active participation, with the development of their research agendas as the basis for progression. To develop this goal, the research metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The course material could be complex, technical, garnering little student interest in the topic, instilling a belief of irrelevancy, and resulting in low student performance (Bell, 2016). And while the mastery of research method courses was one that students within higher education needed to have, there was still an air of dissonance when the thought of taking the course arises.…”
Section: Active Learning Environmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The course material could be complex, technical, garnering little student interest in the topic, instilling a belief of irrelevancy, and resulting in low student performance (Bell, 2016). And while the mastery of research method courses was one that students within higher education needed to have, there was still an air of dissonance when the thought of taking the course arises.…”
Section: Active Learning Environmentsmentioning
confidence: 99%
“…One way to increase engagement within research method courses and to help increase student achievement rates was to take advantage of an intensive course design and active participation (Bell, 2016). The literature reported that the best intensive course designs were those that were in condensed formats that included evening or work-based programs, enlisted the help of an experienced and positive instructor, provided an active-learning environment, and were built around an overall good course organization (Bell, 2016).…”
Section: Active Learning Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase research competencies, it is also critical to foster self-efficacy in research, as well as to offer active participant learning opportunities throughout the course of study (e.g., Bell, 2016;Butcher & Maunder, 2014).…”
Section: Differences In Educational Research Literacy Depending On Stmentioning
confidence: 99%
“…In addition to professional ethics, these students need to develop the research skills necessary to undertake original research in both their degrees and their future careers. An important part of this process is the development of a 'research disposition' (Bell, 2014) [2]. This includes the development of intangible research skills such as due consideration of ethical issues which may impact on the research process.…”
Section: Introductionmentioning
confidence: 99%